2016
DOI: 10.1016/j.cub.2016.04.024
|View full text |Cite
|
Sign up to set email alerts
|

The Minimal Energetic Requirement of Sustained Awareness after Brain Injury

Abstract: Differentiation of the minimally conscious state (MCS) and the unresponsive wakefulness syndrome (UWS) is a persistent clinical challenge [1]. Based on positron emission tomography (PET) studies with [(18)F]-fluorodeoxyglucose (FDG) during sleep and anesthesia, the global cerebral metabolic rate of glucose has been proposed as an indicator of consciousness [2, 3]. Likewise, FDG-PET may contribute to the clinical diagnosis of disorders of consciousness (DOCs) [4, 5]. However, current methods are non-quantitativ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

12
118
3

Year Published

2017
2017
2021
2021

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 102 publications
(133 citation statements)
references
References 19 publications
12
118
3
Order By: Relevance
“…Further, the strength of the relationship between the best brain network metrics we use here and the CRS-R based diagnosis is comparable to that reported in previous literature that has employed EEG-based analysis (King et al, 2013;Sitt et al, 2014). PET (Stender et al, 2016) and TMS-EEG (Casarotto et al, 2016) have been shown to perform better, but both require much more complex technology that is either impossible or difficult to deploy at the patient's bedside. Hence bedside EEG assessments of brain connectivity, potentially estimated with fewer sensors than the high density configuration employed here (Engemann et al, 2015), could valuably complement other neuroimaging technologies.…”
Section: Discussionsupporting
confidence: 64%
See 2 more Smart Citations
“…Further, the strength of the relationship between the best brain network metrics we use here and the CRS-R based diagnosis is comparable to that reported in previous literature that has employed EEG-based analysis (King et al, 2013;Sitt et al, 2014). PET (Stender et al, 2016) and TMS-EEG (Casarotto et al, 2016) have been shown to perform better, but both require much more complex technology that is either impossible or difficult to deploy at the patient's bedside. Hence bedside EEG assessments of brain connectivity, potentially estimated with fewer sensors than the high density configuration employed here (Engemann et al, 2015), could valuably complement other neuroimaging technologies.…”
Section: Discussionsupporting
confidence: 64%
“…We have shown that the progressive re-emergence of connectivity hubs in EEG brain networks, as measured by participation coefficients, tracks the consistency with which consciousness can be measured with the CRS-R, with accuracy comparable to PET-based assessment by an expert. Indeed, the notion that connectivity hubs in specific frontal and parietal loci are important for the recovery of consciousness after brain injury is consistent with evidence from both PET (Stender et al, 2014(Stender et al, , 2015(Stender et al, , 2016 and functional MRI (Vanhaudenhuyse et al, 2010b;Achard et al, 2012). Further, as patients recover beyond MCS, it appears that both positive and negative correlations of activity within and between networks also reappear (Thibaut et al, 2012;Di Perri et al, 2016).…”
Section: Discussionsupporting
confidence: 53%
See 1 more Smart Citation
“…The reverse question is whether neural energy can regulate the state of neural activities. Its scientific significance is that the evolution of neural energy at subthreshold state is directly related to the changes in the neural dark energy in the default mode network, so whether neural energy can modulate the state of neural activity as well as the study of the nature of consciousness has an important scientific significance [23,24]. As far as our current literature is concerned, this problem has not attracted enough attention from neuroscientists, which is because the widely used H-H model is based on a basic assumption that the operation of the ion pump can ensure that the Nernst potential is constant [25].…”
Section: Introductionmentioning
confidence: 99%
“…Notwithstanding the power of these techniques, their application remains a difficult methodological and practical challenge in most medical and care or rehabilitation contexts and might also lead to unreliable results in patients who have problems focusing on specific assessment stimuli or following verbal instructions (Bodien and Giacino 2016;Edlow et al 2013;Harrison and Connolly 2013;Mashour and Avidan 2013;Vul and Pashler 2012). A similarly powerful and complex alternative to fMRI in this assessment area is positron emission tomography (PET) (Giacino et al 2014;Rosanova et al 2012;Stender et al 2014Stender et al , 2016.…”
Section: Assessment Proceduresmentioning
confidence: 99%